Pelaksanaan Progam Kampanye Sadar Wisata dan Sapta Pesona melalui Pelestarian Kelompok Sadar Wisata ( Pokdarwis ) di Kelurahan Kandri Kecamatan Gunungpati Kota Semarang - Asri Nurul Utami; Amni Zarkasyi Rahman (Journal of Public Policy and Management Review, 2017)
Sadar wisata and Sapta Pesona progam is a program that aims to move the area to be ready to receive tourists, in the form of community empowerment through conservation activities carried out by Disbudpar Pokdarwis Semarang to create a conducive climate for growth and development of tourism, especially in Sub Kandri. The purpose of this research is to know how the activity implementation of preservation Pokdarwis in Kandri Village based on technical guidelines of the implementer activity, where the succes measurement is seen in three things those are activity, creation effort and coordination institution. The next purpose was to describe the motivating factors and demotivating of activity based on Grindle’theory. The method which used is descriptive qualitative method. The data collection techniques which are done with observation, interview, documentation and the literature study. The informants of this research is staff guidance section of the community Disbudpar of Semarang City and members of Pokdarwis Sukomakmur and Pandanaran in Kandri Village. The result of this research shows the implementation has done well based on technical guidelines of activity, eventhough the result of achievement is not maximum. The factors which be demotivated are the achievement of degrees changed, available resource particulary for human resource quantity and budget, including the loyality level and response of target group. The writer’s suggestions are needed to use of available field, specific allocation budget and strick warning to pokdarwis member which obey the role.